What Makes a Floor Slippery? A Brief Experimental Study of Ceramic Tiles Slip Resistance Depending on Their Properties and Surface Conditions - Ewa Sudoł (MDPI AG, 2021)
The safety of the use of construction facilities should be a priority in today’s busy world, where it is not difficult to get involved in an accident. Most of them, due to the pace at which we live today, are caused by slips, trips, and falls. This work presents a detailed analysis of the resistance of ceramic floors to these events, taking into account the surface properties and conditions (dry/wet), which, as presented, have a significant impact on the final slip resistance values. This study also investigates the relationship between surface roughness and anti-slip properties. According to the obtained results, it can be concluded that the surface roughness is not the main determinant of slip resistance, and the final value of it is influenced by many components that should be considered together and not be neglected when designing the surface finish. Furthermore, based on experimental measurements, it can be noted that the highest slip resistance in both wet and dry conditions showed the unglazed tiles with lapatto finish and the glazed tiles without any extra finish.